Pengaruh Pembiayaan Syariah dan Indeks Pembangunan Manusia (IPM) Terhadap Tingkat Kemiskinan Di Provinsi Aceh: Analisis Data Panel - Rohmi, Misfi Laili; Jaya, Tiara Juliana (Jurnal Ilmiah Ekonomi Islam, 2021)
Poverty is a significant problem faced by developing countries, including Indonesia. Islam teaches its people to fight poverty because poverty is closer to kufr. Aceh is famous for applying Islamic law, but Aceh is the poorest province on the island of Sumatra in 2020. Meanwhile, in terms of Sharia financing, Aceh Province ranks 4th, and the Human Development Index (IPM) ranks 11th highest nationally. This panel aims to determine the effect of Islamic financing and the Human Development Index (HDI) on poverty levels in Aceh Province. Data analysis was carried out using panel data regression by choosing the best regression model, namely the Fixed Effect Model, by combining cross-section data of 21 districts/cities in Aceh Province during the 2016-2020 period. The study results, both partially and simultaneously, Islamic financing and HDI have a negative and significant effect on the poverty level in Aceh Province.